Factor structures across countries and across clusters of countries: A 36-country study on the Family Values Scale - Mylonas, Kostas (Advances in Social Sciences Research Journal, 2016)
Values in the family have been studied within countries and across-countries with respect to their change, transmission, with relation to familial-individual aspects (family roles, psychological bonds, etc.) and with respect to numerous other psychological correlates. To study values across cultures, factor equivalence is of essence. We employed an alternative methodological and statistical factor equivalence approach across our national samples derived from the Georgas et al. dataset on Family related variables (N=7,766 university students). Apart from the individual country level comparison, a country-clustering method was also applied. For these clusters of countries it was shown through covariance structure analysis that the levels of factor equivalence for the respective factor structure were better and the structure was much clearer as compared to the respective solution with countries treated under the same factor estimation methods but as separate units (not clustered). Conclusions are drawn on family values' support and country/cluster characteristics and on the structural homogeneity of cultures within each cluster.